[PP.36.02]: THE INFLUENCE OF SLOW BREATHING TRAINING ON THE PREVALENCE OF ORTHOSTATIC HYPOTENSION IN CHRONIC HEART FAILURE. STUDY DESIGN AND INTERMEDIATE RESULTS. (June 2015) - Drozdz>, T.>; Bilo, G.; Debicka-Dabrowska, D.; Styczkiewicz, K.; Malfatto, G.; Bednarek, A.; Kielbasa, G.; Czarnecka, D.; Parati, G.; Kawecka-Jaszcz, K.
Abstract : Objective: Slow breathing training (SBT) has been proposed as a new nonpharmacological treatment able to induce favorable effects in chronic heart failure (CHF) patients. However, no information is available regarding its effects on orthostatic blood pressure (BP) changes. Aim of this study was to test the prevalence of orthostatic hypotension (OH) in CHF patients undergoing SBT. Design and method: This analysis was performed in the frame of an ongoing cross-over open trial aimed at assessing the clinical effectiveness of SBT. Patients, in random order, undergo a 10–12 week period of SBT with RESPeRATE device (InterCure Ltd., Lod, Israel) and a 10–12 week follow-up under usual care. Patients randomized to SBT are asked to perform each day two separate 15-min sessions of device-guided SBT at a breathing frequency of 6 breaths per minute. In all patients, before the enrollment and after each phase clinical data collection, BP measurements are performed in supine and standing position. OH is defined as a decrease of > = 20 mmHg in systolic (S)BP or > = 10 mmHg in diastolic (D)BP within 3 minutes of standing. Results: Until now 76 pts have entered the study with the following baseline characteristics: age 64 ± 12 years, 62 M/14F, 29 with ischemic CHF, 39 in NYHA Class II, left ventricular ejection fraction 29.5 ± 7%, 23 with hypertension, 5 with history of stroke, 16 with diabetes. So far 39 of them have completed the study. There were no significant differences in SBP and DBP values in both supine and standing positions among baseline, SBT and control periods (Tab.1). OH prevalence was low and did not change between the phases of the study (3 vs. 2 vs. 3 patients, p = 0.27). The average changes in SBP and DBP after changing position were also not significant: -2.6 ± 12.5 vs –1.2 ± 11.0 vs -2.8 ± 15.3, p = 0.88 and + 3.7 ± 8.5 vs. + 0.9 ± 7.4 vs + 3.7 ± 9.1, p = 0.34 respectively. Figure. No caption available. Conclusions: Preliminary data indicate that SBT is safe and does not affect the prevalence of OH in CHF subjects. If these results are confirmed in a larger sample, they may support the safety of SBT as a novel component of cardiorespiratory rehabilitation programs in CHF.